Responses of Diabetes Mellitus Patients Who Used Complementary Medicine - Anita Joeliantina; Mangestuti Agil; M. Bagus Qomaruddin; Arijanto Jonosewojo; Kusnanto Kusnanto (Intelektual Pustaka Media Utama, 2016)
Diabetes Mellitus as a chronic disease tend to seek appropriate medical treatment to heal the condition. Health-seek searched can be either medical treatment or Complementary and Alternative Medicine. This study explored deeply on the response of diabetes mellituspatients who visited to Indonesian Traditional Medicine Polyclinic on Regional Public Hospital dr. Soetomo Surabaya in using complementary medicine. This study used qualitative study with phenomenological method approach. The focus of this study was diabetes mellitus patients who use complementary medicine. Nine participants were selected based on purposive sampling method with certain criteria. Data collection used was in-depth interview and field note. Data analysis used thematic content analysis. Determining five themes that correspond with the purpose of study and a new theme. Some themes were psychological response after being diagnosed diabetes mellitus, opinion on the diabetes mellitus disease, complementary medicine usage patterns, reasons, the response after the use of complementary medicine, and family support. As a chronic disease, patients need proper treatment and conduct it continuously. Healer shopping was often taken by diabetes mellituspatients. It was required cooperation between patients and health professionals to monitor the behavior in order to achieve the effectiveness of medical treatment.